Histamine deficiency promotes accumulation of immunosuppressive immature myeloid cells and growth of murine gliomas - Ahn, Brian (Oncoimmunology, 2015)
To elucidate mechanisms underlying epidemiological findings of decreased risk of glioma development in patients with allergies and asthma, gliomas were induced in mice deficient for histidine decarboxylase (HDC), the enzyme responsible for histamine production. These mice exhibited shortened survival and enhanced tumor growth compared to wild-type (WT) mice. Previous studies have shown a pivotal role of HDC in maturation of bone marrow (BM)-derived myeloid cells. In our glioma models, brain-infiltrating leukocytes (BIL) demonstrated an increased frequency of CD11b(+)Gr1(+) immature myeloid cells (IMC; both CD11b(+)Ly6G(+) and CD11b(+)Ly6C(+) subpopulations) as well as diminished CD8(+) T cell infiltration and their effector functions in HDC(−/−) mice compared with WT mice. Furthermore, HDC(−/−) IMC demonstrated a more profound immune suppression of CD8(+) T cell proliferation and functions associated with increased prostaglandin E2 (PGE2) expression levels. Celecoxib, a cyclooxygenase-2 inhibitor, which is vital for PGE2 production, abrogated suppressive capabilities of HDC(−/−) IMC. In addition, glioma-bearing HDC-eGFP mice, in which HDC promoter drives green fluorescence protein (GFP) expression, exhibited decreased HDC promoter activities in CD11b(+)Gr1(+) cells in the BM, spleen, and intracranial tumor site compared with non-tumor bearing HDC-eGFP mice. Additionally, in vitro culture with glioma supernatants decreased GFP expression in CD11b(+)Gr1(+), CD11b(+)Ly6G(+), and CD11b(+)Ly6C(+) IMC. HDC expression levels inversely correlated with suppressive functions of CD11b(+)Gr1(+) IMC, as GFP(−)CD11b(+)Gr1(+) more profoundly inhibited CD8(+) T cell proliferation compared with CD11b(+)Gr1(+)GFP(+) cells. Taken together, these data show a significant role of HDC in the glioma microenvironment via maturation of myeloid cells and resulting activation of CD8(+) T cells.